Prophylactic Faecalibacterium prausnitzii treatment prevents the acute breakdown of colonic epithelial barrier in a preclinical model of pelvic radiation disease. Issue 1 (9th November 2020) - Lapiere, Alexia; Geiger, Mallia; Robert, Véronique; Demarquay, Christelle; Auger, Sandrine; Chadi, Sead; Benadjaoud, Mohamedamine; Fernandes, Gabriel; Milliat, Fabien; Langella, Philippe; Benderitter, Marc; Chatel, Jean-Marc; et al.
ABSTRACT: Every year, millions of people around the world benefit from radiation therapy to treat cancers localized in the pelvic area. Damage to healthy tissue in the radiation field can cause undesirable toxic effects leading to gastrointestinal complications called pelvic radiation disease. A change in the composition and/or function of the microbiota could contribute to radiation-induced gastrointestinal toxicity. In this study, we tested the prophylactic effect of a new generation of probiotic like Faecalibacterium prausnitzii ( F. prausnitzii ) on acute radiation-induced colonic lesions. Experiments were carried out in a preclinical model of pelvic radiation disease. Rats were locally irradiated at 29 Gray in the colon resulting in colonic epithelial barrier rupture. Three days before the irradiation and up to 3 d after the irradiation, the F. prausnitzii A2-165 strain was administered daily (intragastrically) to test its putative protective effects. Results showed that prophylactic F. prausnitzii treatment limits radiation-induced para-cellular hyperpermeability, as well as the infiltration of neutrophils (MPO+ cells) in the colonic mucosa. Moreover, F. prausnitzii treatment reduced the severity of the morphological change of crypts, but also preserved the pool of Sox-9+ stem/progenitor cells, the proliferating epithelial PCNA+ crypt cells and the Dclk1+/IL-25+ differentiated epithelial tuft cells. The benefit of F. prausnitzii was associated with increased production of IL-18 by colonic crypt epithelial cells. Thus, F. prausnitzii treatment protected the epithelial colonic barrier from colorectal irradiation. New-generation probiotics may be promising prophylactic treatments to reduce acute side effects in patients treated with radiation therapy and may improve their quality of life.